(untitled) (Asian Journal of Social Science Studies, 2022)
The IFLA Marketing Award is one of the most prestigious awards in the global library industry. Since its inception in 2003, the IFLA Marketing Award has been successfully awarded for 18 years. This paper adopts the content analysis method to analyze the strategic objectives, marketing strategies and the values behind the marketing projects from the library strategic by collating all the prize-winning cases of international Library marketing from 2003 to 2021. It is found that the winners have the characteristics of keeping up with international trends in marketing strategies, marketing core to meet mainstream values, diversifying marketing target groups and subverting traditional marketing methods. This paper proposes that every country‟s libraries should actively respond to IFLA’s „value call‟, improving services through community participation, lead innovation with open borders, and drive development with information technology, so as to provide reference for the marketing of every country‟s libraries.